RTHP-20. MULTI-INSTITUTIONAL ANALYSIS OF HIGH-RISK WHO GRADE II OLIGODENDROGLIOMA TREATED WITH ADJUVANT RADIOTHERAPY PLUS TEMOZOLOMIDE (TMZ) VERSUS PROCARBAZINE, LOMUSTINE, AND VINCRISTINE (PCV). (11th November 2019) - Tom, Martin; Routman, David; Laack, Nadia; Frechette, Kelsey; Park, Deborah; (Auston) Wei, Wei; Leyrer, Marc; Peereboom, David; Ahluwalia, Manmeet; Chao, Samuel; Suh, John; Murphy, Erin
Abstract: PURPOSE: To compare outcomes of adults with high-risk grade II oligodendroglioma treated with adjuvant radiotherapy plus adjunctive TMZ versus PCV. METHODS: We queried a multi-institutional database from the Cleveland Clinic and Mayo Clinic of 158 adults with WHO grade II glioma who were high-risk (age > 40 and/or subtotal-resection [STR]) and underwent adjuvant chemoradiation (TMZ or PCV) between 1997–2017. We included patients with oligodendroglioma by 1p/19q-codeletion or traditional histopathology. Fisher's exact test was used to associate factors with chemotherapy group. The log-rank test was used to compare OS and PFS by chemotherapy group and clinical characteristics. RESULTS: 52 patients were included with a median follow-up of 44 months (range, 3–259). Median age was 44 (range, 22–73), 49 (94%) underwent STR, and 28 (54%) were male. Presenting symptoms were seizure in 35 (67%) patients, sensory in 14 (27%), and motor in 8 (15%). Oligodendroglioma classification was by 1p/19q-codeletion in 27 (52%) and traditional histopathology in 25 (48%) patients. Median radiation dose was 54 Gy (range, 45–60). Chemotherapy was TMZ in 34 (65%) patients and PCV in 18 (35%). Patients who were older ( P =0.003), lacked seizures ( P =0.03), or had motor symptoms ( P =0.04) were more likely to receive TMZ. Median OS was 223 months (95% CI, 181-not estimable) and median PFS was 118 months (95% CI, 69–223). Treatment with TMZ versus PCV was not associated with OS (median 186 vs. 223 months, respectively; P =0.71) or PFS (median 110 vs. 131 months, respectively; P =0.19). Age >40 ( P =0.009) and motor symptoms ( P =0.027) were associated with adverse OS. Presence of motor symptoms was associated with worse PFS ( P =0.008). CONCLUSION: There was no statistically significant difference in OS or PFS between adjunctive TMZ versus PCV for adult high-risk grade II oligodendroglioma. A larger cohort with longer follow-up will provide additional insight.